2017
DOI: 10.1016/j.bbadis.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

EGCG ameliorates diet-induced metabolic syndrome associating with the circadian clock

Abstract: In response to the daily light-dark (LD) cycle, organisms on Earth have evolved with the approximately 24-h endogenous oscillations to coordinate behavioral and physiological processes, including feeding, sleep, and metabolism homeostasis. Circadian desynchrony triggered by an energy-dense diet rich in fats and fructose is intimately connected with a series of metabolic disorders. Previous studies revealed that (-)-Epigallocatechin-3-gallate (EGCG) could mitigate metabolic misalignment; however, only a few rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 44 publications
1
93
0
Order By: Relevance
“…A recent research exhibited that supplementary of EGCG altered diurnally oscillating expression pattern of key appetite‐regulating genes as well as key circadian genes like Clock and Bmal1 in hypothalamus of mice . Furthermore, our previous studies have revealed that EGCG, the most abundant catechin in green tea, may ameliorate HFFD‐induced obesity and metabolic disorders via circadian clock related mechanisms . As a continuous study to further explore the causal relationship and mechanism between the circadian clock and insulin resistance upon EGCG treatment, 50 μM EGCG was used to investigate the mechanism of EGCG against insulin resistance and results showed that EGCG co‐treatment resulted in an improvement in diurnal rhythm of the circadian clock gene under insulin‐resistance conditions (Figures and A).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent research exhibited that supplementary of EGCG altered diurnally oscillating expression pattern of key appetite‐regulating genes as well as key circadian genes like Clock and Bmal1 in hypothalamus of mice . Furthermore, our previous studies have revealed that EGCG, the most abundant catechin in green tea, may ameliorate HFFD‐induced obesity and metabolic disorders via circadian clock related mechanisms . As a continuous study to further explore the causal relationship and mechanism between the circadian clock and insulin resistance upon EGCG treatment, 50 μM EGCG was used to investigate the mechanism of EGCG against insulin resistance and results showed that EGCG co‐treatment resulted in an improvement in diurnal rhythm of the circadian clock gene under insulin‐resistance conditions (Figures and A).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of EGCG (50 μM) in the circulation after dietary intake is so difficult to attain. Fortunately, our previous study revealed that 2 g/L EGCG for 16 weeks in C57BL/6J mice exerted pleiotropic beneficial effects on obesity, circadian desynchrony, and insulin resistance . Based on allometric scaling, the used dose of 2 g/L EGCG in drinking water in mice approximate corresponds to 9 cups of green tea (containing 2 g tea leaves per cup) per day for an average person requiring 2000 kcal/day, which may represent an attainable dose .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations